Diversidade e sazonalidade de ácaros (Acari) em seringal (Hevea brasiliensis, Muell. Arg.) no Noroeste do Estado de São Paulo - Hernandes, Fabio A. [UNESP]; Feres, Reinaldo J. F. [UNESP] (Neotropical Entomology, 2006)
Brazilian southeastern region has soil and climate conditions suitable for the growing of rubber trees, and most part of national yield arises from São Paulo State. The aims proposed for this work were to determine the diversity, the richness and the seasonal occurrence of mites found in a rubber tree crop in a triennial survey with monthly samplings, as well as to estimate the populational density of the major phytophagous species. This study found 74,407 mites from 26 species belonging to 10 families. The phytophagous and predators represented 95.4% and 3.9% of the total abundance, respectively. Twelve species were rare, six accessories and eight constant. The families Phytoseiidae and Tydeidae had the greatest richness (five and four species, respectively). The most numerous species was Calacarus heveae Feres (50,573), with great abundance at the end of rainy season until the beginning of dry season. Among predators, the most abundant were Zetzellia quasagistemas Hernandes & Feres (1,345), Pronematus sp. (455), Zetzellia agistzellia Hernandes & Feres (409) and Euseius citrifolius Denmark & Muma (243). C. heveae had greatest densities on March and April 2003, and Lorryia formosa Cooreman and Tenuipalpus heveae Baker on March and May 2001, respectively. Many stigmaeids were observed in association with colonies of L. formosa preying their eggs and immatures.

A Região Sudeste do Brasil apresenta aspectos edafo-climáticos favoráveis para o plantio e desenvolvimento da seringueira, sendo o estado de São Paulo o maior produtor nacional de látex. Este trabalho teve como objetivos determinar, através de coletas mensais durante três anos de estudo, a diversidade, a riqueza de espécies e a sua sazonalidade, bem como realizar estimativas de densidade populacional das principais espécies de ácaros presentes nas folhas. Todos os ácaros foram montados em lâminas de microscopia, totalizando 74.407 indivíduos, de 26 espécies pertencentes a 10 famílias. Os fitófagos representaram 95,4% do total de indivíduos coletados e os predadores 3,9%. Doze espécies foram consideradas acidentais, seis foram acessórias e oito constantes. Apresentaram maior número de espécies as famílias Phytoseiidae (cinco) e Tydeidae (quatro). A espécie mais abundante foi Calacarus heveae Feres (50.573), com maior abundância nos meses correspondentes ao término da estação chuvosa e início da estação seca na região. Dentre os predadores, a mais abundante foi Zetzellia quasagistemas Hernandes & Feres (1.345), seguida por Pronematus sp. (455), Zetzellia agistzellia Hernandes & Feres (409) e Euseius citrifolius Denmark & Muma (243). C. heveae apresentou maior densidade populacional em março e abril de 2003, e Lorryia formosa Cooreman e Tenuipalpus heveae Baker em março e maio de 2001, respectivamente. Muitos estigmeídeos foram observados associados a agrupamentos de L. formosa predando seus ovos e estágios imaturos.
Diversity and seasonal occurrence of mites (Acari) in a rubber tree crop (Hevea brasiliensis, Muell. Arg.) in northwestern São Paulo, Brazil
Keywords: Biodiversity; Mite fauna; Ecologycal pattern; Biodiversidade; Acarofauna; Padrão ecológico